Strategi Media Relations Humas Bmkg Dalam Menjaga Hubungan Dengan Pers - Karine, Delia Devarly; Solahudin, Dindin; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to determine the management of relations with the media in maintaining relations with the press; to find out the development of a media relations strategy with the press at BMKG; to find out the development of networks with mass media at BMKG. This study uses a descriptive method using a qualitative approach. Source of data comes from primary data and secondary data. The theory used is media relations theory (concepts, approaches and practices). Based on the research results, the results obtained are First, relationship management is carried out by carrying out teamwork, the process of managing relationships and activities; Second, developing a strategy is carried out by developing infrastructure and observing the media; Third, developing networks is done by joining professional organizations.